Prospective evaluation of the multisensor HeartLogic algorithm for heart failure monitoring. Issue 7 (18th April 2020) - Santini, Luca; D'Onofrio, Antonio; Dello Russo, Antonio; Calò, Leonardo; Pecora, Domenico; Favale, Stefano; Petracci, Barbara; Molon, Giulio; Bianchi, Valter; De Ruvo, Ermenegildo; Ammirati, Fabrizio; La Greca, Carmelo; et al.
Abstract: Background: The HeartLogic algorithm measures data from multiple implantable cardioverter‐defibrillator‐based sensors and combines them into a single index. The associated alert has proved to be a sensitive and timely predictor of impending heart failure (HF) decompensation. Hypothesis: We describe a multicenter experience of remote HF management by means of HeartLogic and appraise the value of an alert‐based follow‐up strategy. Methods: The alert was activated in 104 patients. All patients were followed up according to a standardized protocol that included remote data reviews and patient phone contacts every month and at the time of alerts. In‐office examinations were performed every 6 months or when deemed necessary. Results: During a median follow‐up of 13 (10–16) months, the overall number of HF hospitalizations was 16 (rate 0.15 hospitalizations/patient‐year) and 100 alerts were reported in 53 patients. Sixty alerts were judged clinically meaningful, and were associated with multiple HF‐related conditions. In 48 of the 60 alerts, the clinician was not previously aware of the condition. Of these 48 alerts, 43 triggered clinical actions. The rate of alerts judged nonclinically meaningful was 0.37/patient‐year, and the rate of hospitalizations not associated with an alert was 0.05/patient‐year. Centers performed remote follow‐up assessments of 1113 scheduled monthly transmissions (10.3/patient‐year) and 100 alerts (0.93/patient‐year). Monthly remote data review allowed to detect 11 (1%) HF events requiring clinical actions (vs 43% actionable alerts, P < .001). Conclusions: HeartLogic allowed relevant HF‐related clinical conditions to be identified remotely and enabled effective clinical actions to be taken; the rates of unexplained alerts and undetected HF events were low. An alert‐based management strategy seemed more efficient than a scheduled monthly remote follow‐up scheme.